Outcome of TRAP Sequence Treated in the First Trimester – A Ten-Year Single-Center Experience - Weber, Eva Christin; Recker, Florian; Gottschalk, Ingo; Strizek, Brigitte; Geipel, Annegret; Gembruch, Ulrich; Berg, Christoph (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To evaluate the outcome of first trimester intervention by intrafetal laser (IFL) in pregnancies complicated by twin reversed arterial perfusion (TRAP).Materials and Methods For a 10-year study period, all patients with TRAP diagnosed < 14.0 weeks of gestation were retrospectively analyzed for intrauterine course and outcome. Monoamniotic pregnancies were excluded. Patients were offered either intervention by IFL in the first trimester, expectant management, or termination of pregnancy (TOP). Adverse outcome was defined as either intrauterine death (IUD), neonatal death, or preterm birth.Results In 45 cases TRAP was diagnosed. 17 monoamniotics were excluded. The cohort was divided into two groups according to management. Group A: 24 cases underwent IFL and group B: 4 cases were managed expectantly. No patient opted for TOP. In group A, 70.8 % of pump twins were born alive, including one preterm delivery, and 29.2 % died within four days after the intervention. All 4 expectantly managed cases in group B had an adverse outcome (1 preterm delivery, 3 IUDs < 15.0 weeks). There were no neonatal deaths. In cases treated by IFL, a comparison of survivors and non-survivors identified no significant differences in gestational age at IFL or any of the assessed biometrical and functional parameters. There was a trend towards better outcome in the second half of the study period.Conclusion IFL in first trimester TRAP sequence is technically feasible but is associated with significant mortality, albeit less than previously reported. No risk stratification is possible using the investigated parameters. However, there seems to be a learning curve.
Keywords: TRAP sequence; intrafetal laser; monochorionic pregnancy; first trimester; twin reversed arterial perfusion